2014
DOI: 10.1016/j.solmat.2013.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of compensation on the boron and oxygen-related degradation of upgraded metallurgical-grade silicon solar cells

Abstract: Abstract:This paper deals with the impact of dopant compensation on the degradation of carrier lifetime and solar cells performance due to the boron-oxygen defect. The boron-oxygen defect density evaluated by lifetime measurements before and after degradation is systematically found proportional to the total boron concentration, showing that compensation cannot reduce light-induced degradation. This result is confirmed by a comparison of upgraded-metallurgical grade silicon solar cells having identical boron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Looking at figure 2 a higher loss in V oc is observed for the UMG-Si PERC cell than for the poly-Si PERC cell, confirming the hypothesis of Forster et al [12] who observed a correlation between LID and the total boron concentration in UMG-Si. On the contrary other authors found the LID of UMG-Si to correlate with the net doping p 0 [13,14].…”
Section: Light Induced Degradationsupporting
confidence: 83%
“…Looking at figure 2 a higher loss in V oc is observed for the UMG-Si PERC cell than for the poly-Si PERC cell, confirming the hypothesis of Forster et al [12] who observed a correlation between LID and the total boron concentration in UMG-Si. On the contrary other authors found the LID of UMG-Si to correlate with the net doping p 0 [13,14].…”
Section: Light Induced Degradationsupporting
confidence: 83%
“…Thanks to the improvements in the UMG purification process, Zheng et al, in 2016 [7] reported solar cells fabricated with 100% UMG-Si with peak efficiency of 20.9%, and 21.9% for a control device made from electronic grade silicon. Nevertheless, the potential advantage of low cost can be impaired if outdoor efficiency is reduced by degradation of quality due to high concentration of metallic and non-metallic impurities [8]. Manufacturers have started producing PV cells made of UMG-Si, and demonstration projects have been launched.…”
Section: Introductionmentioning
confidence: 99%
“…The studies revealed that the LID in the boron-doped p-type Cz-Si is mainly caused by the strong recombination centers, boron-oxygen (B-O) complexes, which are formed or activated in the condition of excess carrier injection [3,5]. The LID currently represents one of the major mechanisms of the efficiency loss of the state-of-the-art p-type c-Si solar cells [6,7]. n-type silicon has been proven to have a higher tolerance to common transition metal impurities and a lower extent of LID due to the lack of B-O related defects [8][9][10][11][12], showing the potential to replace the p-type Si in the photovoltaic industry, as shown in the International Technology Roadmap for Photovoltaics [13].…”
Section: Introductionmentioning
confidence: 99%